ANALISIS KETERCAPAIAN SIKAP DI SMP MATHLA’UL ANWAR MARGAHAYU - Icmiati Santika; Chaerul Rohman; Dindin Jamaluddin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This research was conducted to measure the attainment of respect for parents, humility, frugality and simple life. It is important to discuss recall is one of the competencies that must be achieved by the participant students in junior high school. This research method uses descriptive quantitative methods, with the amount of participation of 23 people from 8 class D junior Mathla'ul Anwar Margahayu Bandung regency. The instrument used in this study is a questionnaire sheet with 10 indicators to measure the attitudes of students. The conclusions of this study are (1) the overall attitude of the students shows a variety of results with an average achievement of 61%. (2) indicators that have not reached the maximum score are humble, frugal and simple living attitudes. The recommendation of this research is the need for special attention from parents to instill this character through proper parenting for teenagers.